No Permanent Friend or Enemy: Impacts of the IIoT-Based Platform in the Maintenance Service Market - Pei, Jun; Yan, Ping; Kumar, Subodha (Management Science, 2023)
As the industrial Internet-of-things (IIoT) is becoming increasingly valuable, manufacturers are eager to establish IIoT-based platforms for preventative maintenance (PM). These platforms reposition the roles of manufacturers and reshape the patterns of the after-sales service market. Manufacturers can adopt either the competitive strategy by introducing improved after-sales services to compete with independent maintenance, repair, and operations firms (MROs) or the “coopetitive” strategy by simultaneously opening the platform to these MROs. However, relevant research on this topic remains scarce. Hence, our study fills this gap by investigating a manufacturer’s decision for the IIoT-based platform and the subsequent relationship with an MRO. First, we find that even when the product value is relatively low and the IIoT adoption increases PM cost; interestingly, it is sometimes beneficial for the manufacturer to establish the platform. Next, we find that even if the royalty revenue is lower than the increased IIoT costs, the manufacturer may sometimes still adopt the coopetitive strategy of opening the platform. Moreover, with the opening of the platform, the manufacturer pays more technology investment, even in the competitive market. Furthermore, whenever the manufacturer opens the platform, the MRO can profit more by accessing the platform. Hence, there is sometimes a win-win equilibrium with the IIoT adoption. In addition, we find that the opening of the platform sometimes causes less customer surplus but generates more social welfare. Following the IIoT adoption, our findings offer insightful takeaways for the manufacturer’s decisions on the establishment and opening of the platform, the MRO’s reaction, and policymakers’ welfare policies. This paper was accepted by Jeannette Song, operations management. Funding: This work was supported by the National Natural Science Foundation of China [Grants 71922009, 72188101, 71871080, and 72071057]. Supplemental Material: The data files and online appendices are available at https://doi.org/10.1287/mnsc.2023.4733 .